Case Report: Clinical Features of a Case of Suspected Borrelia miyamotoi Disease in Hokkaido, Japan - Yamano, Kimiaki; Ito, Takuya; Kiyanagi, Kaori; Yamazaki, Hirotaka; Sugawara, Mutsubu; Saito, Takashige; Ohashi, Norio; Zamoto-Niikura, Aya; Sato, Kozue; Kawabata, Hiroki (The American journal of tropical medicine and hygiene, 2017)
We herein report a case of suspected Borrelia miyamotoi disease in Hokkaido, Japan. The patient complained of lassitude, arthralgia, and high fever after a tick bite. Furthermore, at the time of consultation, the patient exhibited momentary loss of consciousness and low blood pressure. Laboratory tests revealed elevation of liver enzymes, thrombocytopenia, and increased C-reactive protein. Seroconversion to B. miyamotoi glycerophosphoryl diester phosphodiesterase antigen suggested the patient was infected with a relapsing fever group Borrelia species.